Battery charger based on double-buck and boost converter - Milanovič, Miro (Informacije MIDEM, 2000)
The paper describes a double-back and boost converter structure suittable for battery charger in electrical vehicle application. It is very convenient to use inverter elements for battery charging task. Different DC to DC converter structures can be organized from the inverter semiconductor elements. In the case of the induction motor electrical drive application, the required inductors could be established from the motor windings. Such combined converter should satisfy the unity power factor operation as well. By using the double-buck circuit the current high harmonic disortion will be either avoided or significantly reduced. The boost converter established from the inverter elements the energy transfer from the mains to the load during the whole mains voltage half period. Such combined converter does not need any additional semiconductor or inductor elements except the diode bridge.
Keywords: akumulatorji; polnilniki; pretvorniki; regulatorji